PENERAPAN IZIN USAHA MIKRO DAN KECIL DI KECAMATAN TAMPAN PEKANBARU - Ayu Lestari Nadela; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Implementation of Micro and Small Business License (IUMK) in Tampan sub-district Pekanbaru City has been running since it is launched in November 2015. To facilitate the society to get this IUMK, the government makes the policy that can be handled in the district office where its business is located. And also to facilitate the permissions process, by way of free IUMK management. The purpose of this IUMK is to facilitate the public in obtaining the legality of its business and easy access to capital. The purpose of this study is to find out how the implementation of Micro and Small Business License in Tampan sub-district and what are the factors that inhibit the application of IUMK in Tampan sub-district.This study is conducted by using descriptive qualitative method. By using Syafiie theory that consists of planning, organizing, implementing, and monitoring to determine and to reach the target goal. The informants in this study are Department of Cooperatives, Small and Medium Enterprises of Pekanbaru City, Office of Tampan sub-district, BRI, IUMK and PUMK Assistant (Small and Medium Business Actor).The result showed that the application of IUMK in Tampan sub-district must have good organizational management that consists of planning, organizing, implementing and monitoring. There are inhibiting factors in the implementation of this Small and Micro Business License. They are the existence of micro and small businesses that do not have permission yet, the time of permission completion thatis not one day but until a week, the existence of a fictitious Business, the lack of socialization, and stagnancy occurs.Keywords: Implementation, Management, Business License